Paspalum chilense (Poaceae, Paspaleae): A new species from southern South America - Catanzaro, María Paz; Bonasora, Marisa Graciela; Speranza, Pablo Rafael; Medina-Nicolas, Marcelo; Valls, José F.m.; Rua, Gabriel Hugo (Phytotaxa, 2015)
Paspalum chilense, a new species from Chile belonging to the informal Notata group, is described and illustrated on the basis of morphological, cytological and molecular evidence. Our evidence supports its affinity with P. barretoi and P. nummularium, from Brazil, from which it probably diverged by vicariant speciation. The limited available material of the new species was previously identified as P. pumilum or P. minus. A new key to the species of the core Notata group is provided.